OHP-023 Differences in Training Required For Hospital Pharmacy Practise in France and Quebec. (12th March 2013) - Guérin, A; Merger, D; Courbon, E; Métras, ME; Lebel, D; Bussières, JF
Abstract : Background: During a one-year internship in a Quebec teaching hospital, a group of French pharmacy interns explored the similarities and differences in training. Purpose: To compare the training required for hospital pharmacy practise in France and in Quebec. Materials and Methods: This is a descriptive comparative study. A list of relevant themes was established by consensus after a review of key websites and literature. A panel of three French interns, a Quebec hospital pharmacy resident and two teaching hospital pharmacists was assembled. Similarities and differences for each theme were identified and discussed. Results: Twenty-seven themes were selected with seven similarities and twenty differences between France and Quebec. In both countries, post-graduate training included a selection process, a structured programme with pre-identified topics, lectures and experiential courses. While post-graduate training is perceived as a plus-value, it is not mandatory. Amongst the differences identified, the two post-graduate systems have been offered for a different period of time (1815-France vs. 1961-Quebec), French interns are not working as pharmacists while Quebec residents are, French internship lasts 4 years vs. 16 months in Quebec, French annual scholar fees are lower (500 euros/year vs. 3840 euros/18 months in Quebec), both programmes offers two paths (hospital/industry in France; hospital/community pharmacy in Quebec), French internship locations includes healthcare agencies, laboratories, research units, hospitals while Quebec residency focuses on patient care locations in hospitals/retail pharmacy and admission capacity differs. Other differences were identified in geographic mobility, resident status, obligations and responsibilities, modalities of supervision, compensation, on-call shifts and evaluation. Conclusions: There are significant differences between French and Quebec post-graduate training although both require work in hospital settings. A better understanding of these similarities and differences may contribute to reciprocal improvement of these programmes and favour exchanges between the two countries. No conflict of interest.